Exploiting the Sadness of Disabled Athletes: (Critical Discourse Analysis of Theo Van Leeuwen on Detik.com January 16, 2022 Edition) - Rahmat Edi Irawan; Kismiyati El Karimah; Merry Fridha Tripalupi (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2022)
Reporting about athletes disables anything new in the world of journalism. In several regional, national, and international sports pages, journalists always write news about the other side of life and his struggles in overcoming disability in the match. It is interesting to see how athletes with disabilities are used as commodities and exploited their interests. So, with this view, the researcher analyzed a text entitled Exploitation of Sadness for Athletes with Disabilities (Theo Van Leeuwen's Critical Discourse Analysis on Detik.Com Edition January 16, 2022). The research uses Frankfurt’s critical theory, with qualitative methods, with a critical analysis approach from Theo Van Leeuwen. The results showed that the writer used several inclusion and exclusion strategies in the news text. The inclusion strategy focuses on Halil exploitation as the main star in the text above. Halil is described as a young man who has limitations and physical imperfections but wins in sports competitions. Meanwhile, in the exclusion strategy, the scriptwriter does not present a coach who has contributed to Halil's victory or a friend from a hawker association who is also an athlete who paved the way for Halil to become an athlete. With this inclusion and exclusion strategy, it can be seen how the perspective of news writers for persons with disabilities places them in an unequal position with humans in general